Corporate Social Responsibility and Urban Development - Werna, E. author. aut Link
VIII, 245 p. 4 illus.
Keywords: Urban development cooperation needs innovative solutions. Despite many efforts, international assistance has failed to address the challenges faced by cities in developing countries. This book seeks to raise awareness about the value of corporate social responsibility as a tool in urban development assistance.